TRANSLATION PROBLEMS OF PHRASEOLOGICAL UNITS WITH A GASTRONOMIC COMPONENT - Abduganiyeva Mohibonu Norbobo qizi (Journals Park Publishing, 2023)
Phraseologisms with a gastronomic component are a kind of conceptual constant, since they exist in any language. National cuisine, its symbolism, terminology play an important role in comprehending and interpreting culture as a system in which the past, present and future coexist, leading an ongoing dialogue. In the intercultural aspect, this dialogue includes the borrowing of various products and national dishes from one people to another.
Keywords: phraseology, gastronomic phraseological units, national-cultural specificity, interlingual relations, examples.